Penguatan Nilai-Nilai Religius di Perguruan Tinggi - Yulianti Yulianti; Stephani Raihana Hamdan; Dian Widya Putri (MediaTor (Jurnal Komunikasi), 2018)
Globalization and technological development has impact on competition for the excellence in all aspects of life, including in the field of education. Education is the main basis of a nation’s strategy to rise from adversity. Bandung Islamic University (Unisba) is one option for parents who not only consider about quality, but also prioritize the application of good religious values. Indeed, the axiom of good student output in the future is closely related to good values, good skills and a good attitude. The ultimate goal of Islamic Education is the emergence of moral guidance, so that it is appropriate to strengthen religious values in Fikom Unisba. This research is related to the efforts to strengthen the religious values carried out by the Faculty of Communication Sciences of Unisba which is use a qualitative approach. The subject of this study was Dr. O. Hasbiansyah as the Dean of the Faculty of Communication, Unisba. Management of religious values instilled in the Faculty of Communication in every aspects. Starting from the curriculum, human resources (lecturer, education staff, and students), as well as the work environment (setting). This is makes Islamic values inseparable from work and service. All of them are integrated in one system, in order to create strenghtening of value as the common goal.